118k views
1 vote
5x-(x+4)=10-2(x-8)
solve for x

User Olleicua
by
6.4k points

1 Answer

3 votes

Answer:

x=5

Explanation:

Simplifying

5x + -1(x + 4) = 10 + -2(x + -8)

Reorder the terms:

5x + -1(4 + x) = 10 + -2(x + -8)

5x + (4 * -1 + x * -1) = 10 + -2(x + -8)

5x + (-4 + -1x) = 10 + -2(x + -8)

Reorder the terms:

-4 + 5x + -1x = 10 + -2(x + -8)

Combine like terms: 5x + -1x = 4x

-4 + 4x = 10 + -2(x + -8)

Reorder the terms:

-4 + 4x = 10 + -2(-8 + x)

-4 + 4x = 10 + (-8 * -2 + x * -2)

-4 + 4x = 10 + (16 + -2x)

Combine like terms: 10 + 16 = 26

-4 + 4x = 26 + -2x

Solving

-4 + 4x = 26 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.

-4 + 4x + 2x = 26 + -2x + 2x

Combine like terms: 4x + 2x = 6x

-4 + 6x = 26 + -2x + 2x

Combine like terms: -2x + 2x = 0

-4 + 6x = 26 + 0

-4 + 6x = 26

Add '4' to each side of the equation.

-4 + 4 + 6x = 26 + 4

Combine like terms: -4 + 4 = 0

0 + 6x = 26 + 4

6x = 26 + 4

Combine like terms: 26 + 4 = 30

6x = 30

Divide each side by '6'.

x = 5

Simplifying

x = 5

User Qkx
by
5.8k points